2021
DOI: 10.3390/diagnostics12010027
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Portable Microwave Imaging Device for Breast Cancer Detection

Abstract: Purpose: Microwave radar-based breast imaging technology utilizes the principle of radar, in which radio waves reflect at the interface between target and normal tissues, which have different permittivities. This study aims to investigate the feasibility and safety of a portable microwave breast imaging device in clinical practice. Materials and methods: We retrospectively collected the imaging data of ten breast cancers in nine women (median age: 66.0 years; range: 37–78 years) who had undergone microwave ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…This section focuses on these key articles that have pushed to estimate the diagnostic performance of BMS. Eleven of these articles provided sensitivity estimates, ranging from 63% [47] to 100% [141,170], but only four articles have estimated the specificity, and specificity estimates range from 20% [100] to 65% [133]. Table 2 describes the diagnostic estimates presented in each of these articles.…”
Section: Estimates Of the Diagnostic Potential Of Image-based Tumour ...mentioning
confidence: 99%
“…This section focuses on these key articles that have pushed to estimate the diagnostic performance of BMS. Eleven of these articles provided sensitivity estimates, ranging from 63% [47] to 100% [141,170], but only four articles have estimated the specificity, and specificity estimates range from 20% [100] to 65% [133]. Table 2 describes the diagnostic estimates presented in each of these articles.…”
Section: Estimates Of the Diagnostic Potential Of Image-based Tumour ...mentioning
confidence: 99%
“…Researchers at Hiroshima University investigated the possibility of developing a handheld impulse-radar breast cancer detector and reported promising results [ 99 ]. Adachi et al [ 128 ] reported on a radar-based portable MWI system for detecting breast cancer. The results showed that the system can be safely used and that it showed great potential in detecting breast cancer, including non-invasive ductal carcinoma and micro-invasive carcinoma, which were not as easily detected by mammography due to dense breast tissue.…”
Section: Challenges and Future Research Directionsmentioning
confidence: 99%
“…Tumor detection in smaller groups of patients with radar systems has also been reported. 15,16 Microwave tomography has been used to examine 43 healthy volunteers, showing bilateral symmetry and correspondence between average microwave properties and breast density. 17 Tomog-raphy images of 150 patients demonstrated increased properties in regions of interest related to the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Both the MammoWave and Wavelia systems require complex signal processing algorithms to obtain results. Tumor detection in smaller groups of patients with radar systems has also been reported 15,16 . Microwave tomography has been used to examine 43 healthy volunteers, showing bilateral symmetry and correspondence between average microwave properties and breast density 17 .…”
Section: Introductionmentioning
confidence: 99%